1979
DOI: 10.1111/j.1600-0773.1979.tb02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hypersensitivity to Tuberculin in Rats: Effects of Antirheumatic Drugs

Abstract: Absfract:The effects of different antirheumatic drugs administered according to various dosing regimes on tuberculin hypersensitivity in rats have been assessed quantitating the changes of exudate volume and mononuclear cells immigration at the site of challenge. Dosing at the time of sensitization with aurothiomalate and D-penicillamine enhanced the cell immigration which was decreased by similar treatment with levamisole. Cyclophosphamide increased the exudate formation. Indomethacin had no effect. Dosing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…While a detailed assessment of hormetic responses of the immune system suggested that most would be beneficial, in about 20% of the cases, the low dose stimulatory response could lead to harmful effects, such as certain autoimmune responses including lupus 75 and tuberculin hypersensitivity. 76 Hormesis in drug discovery, development and in the clinical trial Drug discovery, development and clinical trial efficiency could be significantly enhanced if they were guided by principles derived from an understanding of the concept of hormesis. This is the case for drugs designed to kill harmful agents.…”
Section: Hormesis and Harmful Effectsmentioning
confidence: 99%
“…While a detailed assessment of hormetic responses of the immune system suggested that most would be beneficial, in about 20% of the cases, the low dose stimulatory response could lead to harmful effects, such as certain autoimmune responses including lupus 75 and tuberculin hypersensitivity. 76 Hormesis in drug discovery, development and in the clinical trial Drug discovery, development and clinical trial efficiency could be significantly enhanced if they were guided by principles derived from an understanding of the concept of hormesis. This is the case for drugs designed to kill harmful agents.…”
Section: Hormesis and Harmful Effectsmentioning
confidence: 99%